Impact of Biscuits Fortified with Isolated Sulfated Polysaccharides from Cladophora Fracta: Rheological, Functional and Sensory Properties. - Jasem, Mohanad; Merai, Abd- Alwahab; Nizam, Adnan Ali (Jordan Journal of Agricultural Sciences, 2024)
The research axes are directed toward integrating biotechnology with the manufacture of functional foods. This research aimed to extract sulfated polysaccharides (SPs) from green freshwater algae Cladophora fracta using ultrasonic-assisted extraction methods and acetone 70% as a solvent, then purify it by Sephadex gel G-100 chromatography, and determine its components, also to investigate its effect on the dough rheological properties, and on increasing the antioxidant properties of biscuits. The yield from the extraction process was 12.2%, which was subjected to the purification process to give two fractions F1 and F2. Results show that the purified SPs consists of sugar units, protein, uranic acids, and a sulfate group, based on the near-infrared spectrum (FT-IR). We determined the quantity contents in personages in fractions F1 and F2: (60,68.2)% carbohydrate; (2.41,1.38)% protein; (18.9,10.90)% uronic acids; 8.55,9.5% sulfate respectively, and the antioxidation activity of crude, F1, and, F2 on 10% concentration were (34,35,35.3)%, respectively based on DPPH• test, and (7,18,12)% respectively based on ABTS•+ test. The sugar units consisted of four monosaccharides (galactose 11.8%, rhamnose10.9%, xylose10.3%, and arabinose 12.9%) based on high-performance liquid chromatography (HPLC). Adding purified SPs (F1 and F2) to durum wheat flour at rates of (0.5, 1,1.5)% affected the rheology properties, and changed Farinograph and extensograph indicators. Fractions from SPs are redox agents; they reduce Dough development time and Stability time compared to control, which has development and Stability times of 3.9 and 3.6 minutes, respectively. This addition also increased the extensibility of the dough, the increase in extensibility was accompanied by an increase in the concentration of F1 and F2, and the highest values of extensibility were 158 and 160 mm, respectively when adding F1 and F2 to flour at 1.5% percentages. This indicates an increase in the weakness of the dough, while this addition causes a decrease other than the extensograph indicators. F2 was added in proportions of 0.5, 1, and 1.5% to wheat flour to manufacture biscuits fortified with SPs, the increased percentages of SPs caused darkness for biscuits. The sensory evolution was done, and all reviewers agreed that the treatment with 1 % of F2 was the best in accept, and this addition increased the anti-oxidative activity of fortified biscuits based on the test of DPPH• and ABTS+• throughout the storage period. This increase was accompanied by an increase in the percentage of SPs compared to the control, where the 50% inhibitory concentration scavenging of free radicals 50% (IC50) in the control treatment was 5.37 g/g for the DPPH• test and 5.72 g/g for the ABTS• + test, while the treatment that was used with it 1.5% of F2 was0.16 g/g for the DPPH• test and 0.01 g/g for the ABTS+• test, which did allow the manufactured biscuit to be a functional food.